Stunting and its Determinant Factors Among Children Under Five in North Maluku Province in 2021-2023 - Sita Aulia Wahidah; Rulyta Aulia Ramadanti; Nurul Awaliyah Muharramah; Ikeu Tanziha (Journal of Nutrition Science, 2024)
The occurrence of stunting has become one of the global health challenges, especially in developing countries. The average prevalence of stunting in North Maluku province from 2021 to 2023 is around 24.9% for children under 5 years old. Stunting is a nutritional problem caused by multiple factors. Factors suspected to influence the occurrence of stunting include the diversity of food consumption and food security. Food diversity can be described through the expected food patterns score, while food security can be measured using the food security index indicator. The purpose of this research is to identify the factors causing stunting in North Maluku province from 2021 to 2023. This study uses a cross-sectional design with secondary data sources. Data analysis used Pearson and Spearman correlation as well as multiple linear regression tests. The results of the bivariate data analysis show that the average years of schooling for women (P<0.001) and the ratio of healthcare workers (P<0.001) are significantly related. As for the desirable dietary patterns (P=0.426), the population below the poverty line (P=0.142), food expenditure >65% (P=0.822), lack of access to electricity (P=0.177), lack of access to clean water (P=0.833), and life expectancy (P=0.110), these are variables that do not have a significant relationship. The multivariate analysis results show that the p-value for the average years of schooling for women is 0.005 and the healthcare worker ratio is 0.004. Thus, it can be concluded that there is a significant influence between the average years of schooling for women and the ratio of healthcare workers on the incidence of stunting in children in North Maluku province from 2021 to 2023.